Improved institutional settings promote employment - Herbert Brücker; Maye Ehab Samy; Philipp Jaschke; Yuliya Kosyakova (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Various institutional hurdles such as asy- lum procedures, employment bans and residency restrictions impair the labor market integration of refugees. These hurdles are prevalent particularly at the beginning of their stay, and are re- duced over time, as shown by analyses based on the IAB-BAMF-SOEP Survey of Refugees. Language and other integra- tion programs also gradually facilitate integration into the labor market. This improved integration is reflected in the increase in the employment rate of refu- gees who arrived in 2015 to almost two thirds in 2022.
Keywords: 330; Federal Republic of Germany; asylum procedure; integration course; professional integration; employment development; determinants; development; labor force participation; employment rate; refugees; gender-specific factors; institutional factors; language support; IAB-BAMF-SOEP survey of refugees; place of residence; work ban; 2016-2022